2013
DOI: 10.1108/00400911311326072
|View full text |Cite
|
Sign up to set email alerts
|

CEO business education and firm financial performance: a case for humility rather than hubris

Abstract: Purpose -The purpose of this paper is to examine the relationship between CEO business education and firm financial performance. Design/methodology/approach -An analysis of the relationship between three-year and fiveyear shareholder return as measured by dividend and change in share price and CEO educational qualification was performed. Findings -No relationship was found between CEO MBA, business, or other qualification and firm financial performance.Research limitations/implications -More research, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 60 publications
1
16
2
3
Order By: Relevance
“…That means that the test results consistent with the hypothesis given that the hypothesis can be accepted. However, the results in this study are not consistent with research Lindorff and Jonson (2013), which states that no correlation was found between the companies that own CEO, educated MBA or other qualifications with the company's financial performance.…”
Section: Resultscontrasting
confidence: 56%
“…That means that the test results consistent with the hypothesis given that the hypothesis can be accepted. However, the results in this study are not consistent with research Lindorff and Jonson (2013), which states that no correlation was found between the companies that own CEO, educated MBA or other qualifications with the company's financial performance.…”
Section: Resultscontrasting
confidence: 56%
“…However, Gottesman and Morey (2010) used only a market-based measurement-Tobin's q. Furthermore, Lindorff and Jonson (2013) investigated the impact of CEO business education on performance. The findings indicated that CEO business education does not influence firm performance.…”
Section: Ceo Educationmentioning
confidence: 99%
“…However, Darmadi (2013) stated that in Indonesia, high-performing firms were founded and managed by people who were not highly-educated. Lindorff & Jonson (2013) also found that there were no relationship between business educations of Australia's top 200 CEOs and firm financial performance. Another demographic factor that could influence the firm performance is the director's age, as discovered by Amran, Yusof, Ishak, and Aripin (2014).…”
Section: Introductionmentioning
confidence: 97%